A modeling government revenue guarantees in privately built transportation projects: a risk-adjusted approach - Kokkaew, Nakhon; Chiara, Nicola (Transport, 2013)
Countries around the world have welcomed Public Private Partnerships (PPPs) as an alternative to finance infrastructure. For strategic projects with high demand uncertainty, a government may decide to provide a concessionaire with a Minimum Revenue Guarantee (MRG) to mitigate revenue risk and to help enhance the project’s credit, thereby reducing the financing costs of the project. However, government revenue guarantees can pose fiscal risks to the issuing government if too many significant claims are redeemed at the same time. This undesirable circumstance can be exacerbated during an economic recession in which tax revenues are low and the costs of subsidies are potentially higher than expected. This paper presents a new model of government revenue guarantees by which revenue guarantee thresholds are adjusted over time to reflect the inter-temporal risk profiles of the project. Revenue risk is modeled using a stochastic process called the Variance Model. Then, revenue shortfalls and revenue excesses are modeled as multi-early exercise options, and priced using multi-least squares Monte Carlo method. Finally, an illustrative example of a Build-Operate-Transfer (BOT) highway project demonstrates how the proposed model may be applied in practice at the project evaluation stage. The proposed model may help to promote fairer risk allocation between the host government and the concessionaire. First Published Online: 16 Jul 2013